Enhanced BDNF serum levels in patients with severe pathological gambling. (1st November 2011) - Angelucci, Francesco; Martinotti, Giovanni; Gelfo, Francesca; Righino, Elisabetta; Conte, Gianluigi; Caltagirone, Carlo; Bria, Pietro; Ricci, Valerio
ABSTRACT Although the pathophysiology of gambling is unknown, an involvement of midbrain dopaminergic pathway has been hypothesized. In this study, the association between brain‐derived neurotrophic factor (BDNF) and pathological gambling was investigated. We measured BDNF serum levels in (1) video players (n = 10); (2) card players (n = 9); (3) mixed players (n = 21; both video and card players) and (4) age‐matched controls (n = 18). Mixed players had increased BDNF serum levels as compared to controls and higher South Oaks Gambling Screen score as compared to card or video players. Thus, the data demonstrate that patients affected by severe pathological gambling show enhanced BDNF serum levels.